x+3/x+2+x-3/x-2=2x-3/x-1

Simple and best practice solution for x+3/x+2+x-3/x-2=2x-3/x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+3/x+2+x-3/x-2=2x-3/x-1 equation:



x+3/x+2+x-3/x-2=2x-3/x-1
We move all terms to the left:
x+3/x+2+x-3/x-2-(2x-3/x-1)=0
Domain of the equation: x!=0
x∈R
Domain of the equation: x-1)!=0
x∈R
We add all the numbers together, and all the variables
2x+3/x-3/x-(2x-3/x-1)=0
We get rid of parentheses
2x+3/x-3/x-2x+3/x+1=0
We multiply all the terms by the denominator
2x*x-2x*x+1*x+3-3+3=0
We add all the numbers together, and all the variables
x+2x*x-2x*x+3=0
Wy multiply elements
2x^2-2x^2+x+3=0
We add all the numbers together, and all the variables
x+3=0
We move all terms containing x to the left, all other terms to the right
x=-3

See similar equations:

| x+1/3=214 | | 4.25xx=38.25 | | n/6-4=2 | | 5-m=2.75 | | n+9=274/9 | | -5u+2(u+4)=2 | | -4y=4y-3 | | y/5+8=29 | | 2x+5(2x+9)=12x+45 | | f-3/4=4 | | 0.16(y-9)+0.08y=0.14-2.1 | | 4x/3x=50 | | 0=36x^2-478x-2463 | | 7/9c=20 | | -6n-7=5 | | 3m^2-9m-30=0 | | -1.5y=-12 | | 2/3x-3=x+18 | | -17r+8=-26 | | 6w+9=126 | | (-(3/2))y=-12 | | 8n+-10=6 | | 5x+6/3=2x-6/5+7 | | x^2+13.5^2=(3x)^2 | | 7n-15=36 | | x^2+13.5^2=3x^2 | | 7n—15=36 | | 2/3x-2=4x+18 | | 10=√x^2+2x+65 | | -15=-3+3w | | 9x-51=8x-10 | | 4^x+4^(x-1)=80 |

Equations solver categories